Sitting Bull, 1831-1890 - Todd, Anne M. (Mankato, Minn. : Blue Earth Books, 2003)
Explores the life of the Lakota leader, Sitting Bull, including the battles in which he fought, his surrender and death. Includes activities, sidebars, a map, and a chronology.
Lakota battle for homeland -- A Lakota boy -- Leader for his people -- Struggles with White people -- Lakota fight for their land -- Lakota life changes
Includes bibliographical references and index.
HG 04/03
0710
Keywords: Sitting Bull, -- 1834?-1890 -- Juvenile literature; Sitting Bull, -- 1834?-1890.; Dakota Indians -- Biography -- Juvenile literature; Dakota Indians -- History -- Juvenile literature; Hunkpapa Indians -- Biography -- Juvenile literature; Dakota Indians -- Biography; Dakota Indians -- History; Hunkpapa Indians -- Biography; Indians of North America -- Great Plains -- Biography; Kings, queens, rulers, etc